Clinical & epidemiological profile of malignancy in HIV a retrospective study - Kiran VH; John T Ramapuram; Krishna Prasad (International Journal of Medical Research and Review, 2015)
Background: HIV is the etiologic agent of AIDS. HIV infection is associated with various types of opportunistic infections and malignancies. The incidence of malignancies among Human Immunodeficiency Virus (HIV) infected patients is known to be higher than in the general population. The study was aimed to know the profile of malignancy in HIV infected individuals.Methodology: Study was a Retrospective study & data was collected from medical records department using semi structured proforma. 40 HIV subjects diagnosed with malignancy was obtained. Stastical analysis of data was done using Chi square test and Fisher’s exact test.Results: Out of 40 HIV subjects diagnosed with malignancy in our study 62%, were males and 38% were females, 95% were receiving ART, Predominantly the patients were in STAGE 4 and NHL was the most common malignancy in our study. CD4 count has no correlation with the incidence of malignancy.Conclusion: Age and Gender distribution does not affect the type of malignancy. Non AIDS defining malignancies are more prevalent than AIDS defining malignancies. NHL is the commonest type of AIDS defining malignancy. CD4 count and HIV stage does not predict the type of malignancy, immunodeficiency can be a trigger for development of malignancy.